New M dwarfs found in DFBS plates - Kostandyan, G. R.
In this paper we report about 100 new M dwarfs, confirmed in the DFBS database. The DFBS is the digitized version of the First Byurakan Survey (FBS, or Markarian survey). FBS plates have been used to search and study faint Late-Type Stars (LTS). The confirmations is based on Gaia DR3 BP/RP spectral database. In previous studies of the DFBS plates, these objects were presented as LTS candidates. TESS phased light curves for some of them shows flares. In SEDs of these objects the infrared excess is clearly visible.
Keywords: Astrometry; Space Sciences; Archaeoastronomy and Astronomy in Culture